Gluteal muscle size and quality in professional ballet dancers compared to non-dancing athletes - McMillan, R. M.; Mayes, S.; Cook, J.; Semciw, A. I.; Plass, L. M.; Pizzari, T. (Journal of Dance Medicine & Science, 2023)
Key Points